Rare flavours - V, Ram (BOOM! Studios, 2024)
Discover the tantalizing tale of Rubin Baksh, a demonic Rakshasa with a down-to-earth dream of being the next Anthony Bourdain. To achieve his vision, Rubin enlists Mo, a filmmaker who has seen better days, to document the world-renowned cuisine of India and the people behind such glorious food. But little does Mo know that there's more to Rubin than meets the eye, and the mortals play a darker role in the show than they were prepared for...